The Effect of Content Marketing and Electronic Word of Mouth (e-wom) on Purchasing Decisions of the Tasikmalaya Regency Transportation Office (Survey of University of Perjuangan Tasikmalaya Students Class of 2019 Erigo Cunsomers in The Tiktokshop Applica - Alvisyah Zanatunnisa; Ari Arisman; Barin Barlian (Journal of Indonesian Management, 2023)
This study aims to determine the effect of content marketing and electronic word of mouth simultaneously on purchasing decisions for Erigo stores in the Tiktok shop application. The effect of content marketing and E-wom partially on purchasing decisions at Erigo stores in the Tiktok shop application. The method used in this research is descriptive causal with a quantitative approach. With a research sample of 100 people as respondents to students from the Universitas Perjuangan, Tasikmalaya student class of 2019, based on 989 known population data, the analytical tool used in this study is multiple linear regression using the SPSS support application version 25. Simultaneously content marketing and E-wom have a significant effect on purchasing decisions. The test results show that partially the content marketing variable has a positive but not significant effect on purchasing decisions, but for the E-wom variable it has a partial positive and significant effect on purchasing decisions.